Ion Exchange : Studies and Applications - Kilislioglu, Ayben; Kilislioglu, Ayben (IntechOpen, 2015)
This book provides broad coverage of ion exchange and its applications. Different chapters focus on the importance of ion exchange applications such as strengtening dental porcelains, gradient changes in glass refraction, and resins as effective sorbents. Each chapter includes a brief historical overview of ion exchange and its applications. The authors also give a brief overview of these applications as well as review current experimental data on the subject.
English
Keywords: Spectrum analysis, spectrochemistry, mass spectrometry; Electrochemistry & magnetochemistry